Neutralization map of the hemagglutinin-neuraminidase glycoprotein of Newcastle disease virus: domains recognized by monoclonal antibodies that prevent receptor recognition. - Iorio, R M (1991)
Monoclonal antibodies (MAbs) to the hemagglutinin-neuraminidase (HN) glycoprotein of Newcastle disease virus delineate seven overlapping antigenic sites which form a continuum on the surface of the molecule. Antibodies to five of these sites neutralize viral infectivity principally by preventing attachment of the virion to cellular receptors. Through the identification of single amino acid substitutions in variants which escape neutralization by MAbs to these five antigenic sites, a neutralization map of HN was constructed, identifying several residues that contribute to the epitopes recognized by MAbs which block the attachment function of the molecule. These epitopes are defined, at least in part, by three domains on HN: residues 193 to 201; 345 to 353 (which include the only linear epitope we have identified in HN); and a C-terminal domain composed of residues 494, 513 to 521, and 569. To identify HN residues directly involved in receptor recognition, each of the variants was tested for its ability to agglutinate periodate-modified chicken erythrocytes. One variant with a single amino acid substitution at residue 193 was 2.5- to 3-fold more resistant to periodate treatment of erythrocytes than the wild-type virus, suggesting that this residue influences the binding of virus to a sialic acid-containing receptor(s) on the cell surface.